Noninvasive Polypoid Malignant Mixed Mullerian Tumor of the Uterus: A Case Report and Literature Review - Leon Kaza; Leart Berdica; Teona Teona; Albina Ndoja (Albanian Journal of Trauma and Emergency Surgery)
Introduction: Malignant mixed Müllerian tumors (MMMT), also known as carcinosarcomas, are rare and highly aggressive neoplasms of the uterus, accounting for less than 5% of all uterine malignancies. These tumors are biphasic, comprising both carcinomatous (epithelial) and sarcomatous (mesenchymal) components, and are typically associated with poor prognoses due to their rapid progression and high metastatic potential.